An Investigation into the Effect of Compensation and Benefits (C&B) on Employee Motivation – The Multinational Corporations in Hong Kong - LI, Wing Yan (2017)
This research examines the correlation between Compensation and Benefits (C&B) and employee motivation. It mainly investigates the effects of C&B, especially base salary and paid annual leave, on work motivation level of employees who are working in Hong Kong multinational corporations in accounting, retail and IT industry. A total of 24 individual Skype in-depth interviews are conducted and all targeted interviewees are university graduates with less than two years’ working experience. Interviewees are asked about their current C&B package received, their overall work motivation level, personal working experiences, and their perceptions towards two C&B components which are base salary and paid annual leave. Results and data analysis have suggested that base salary, paid annual leave, and medical insurance are the most important factors to extrinsically motivate employees working in Hong Kong multinational corporations. It is also revealed that C&B poses large effects on Hong Kong employees’ work motivation level as most of them have strong cash mentality. Cash-related compensation are focused by Hong Kong employees, particularly in business industries. Results are discussed in the aspects of classic motivation theories and managerial implications.